The Knowledge and Attitudes of the Public toward the Clinical Use of Artificial Intelligence - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: This study aims to explore the knowledge and attitudes of the public toward the clinical use of artificial intelligence. Materials and Methods: This is a cross-sectional study that included an online questionnaire. The data were collected and analyzed using Excel software and represented as frequencies and percentages. Results: More than 55% of the respondents said that they had heard of artificial intelligence in medicine but only 3.17% said that they know about artificial intelligence in medicine completely. More than 89% of the respondents said that they prefer the suggestions from human doctor to take when diagnosis diverges. Moreover, only 25.34% of them believe in the therapeutic advice made by an artificial intelligence doctor independently. Conclusion: The present study showed that a high percentage of the public was not trust the use of artificial intelligence because they fear that artificial intelligence could cause fatal errors. Further studies are needed to ensure the efficacy of artificial intelligence doctor before the implementation and after that help patients in understanding the benefits and the risk of artificial intelligence use.